Relationship between serum total testosterone and prostate volume in aging men - Bo-Wen Xia (Nature Portfolio, 2021)
Abstract Total testosterone levels decline with age, while prostate volume and the prevalence of benign prostatic hyperplasia increase with age. We sought to investigate the correlation of serum testosterone levels with prostate volume in aging men. We analyzed clinical data obtained from 416 ostensibly healthy men who underwent routine health check-ups and recruited and collected data from these subjects 4 years later. We analyzed the correlation between prostate volume and relevant factors, as well as the correlation between changes in prostate volume and low testosterone over a 4-year period. Men with low testosterone had significantly larger prostate volume than those in the normal testosterone group (26.86 ± 8.75 vs. 24.06 ± 6.77 P = 0.02), and subjects with low testosterone had significantly higher levels of obesity-related factors, including waist circumference, body mass index, and insulin (all P < 0.001). After adjustment for age, testosterone level was negatively correlated with prostate volume (P = 0.004), and prostate volume and 4-year changes in prostate volume were associated with low testosterone. With increased testosterone level, prostate volume showed a significant linear decreasing trend. These findings provide evidence of the relationship between testosterone and prostate volume. Additional large studies are needed to confirm these preliminary results.